Burden of tuberculosis in Europe due to migrant crisis: urgent integration of global health perspectives into national TB control program - Adzic Vukicevic, Tatjana; Stosic, Maja; Milisavljevic, Jovana (Medical Research, 2026)
Global migration has increased in recent decades owing to war, conflict, persecution and natural disasters, but also secondary to increased opportunities related to work or study. Migrants’ risk of tuberculosis (TB) differs depending on migration, socioeconomic status, mode of travel and TB risk in transit, TB incidence and healthcare provision in country of origin. A narrative review summarized current evidence on the diagnosis of active TB in migrants entering the European Union/European Economic Area and UK, including clinical presentation and diagnostic delay, treatment outcomes of drug-susceptible TB and multidrug-resistant/ rifampicin-resistant TB, prevalence and TB/ humam immunodeficiency virus (HIV) co-infection. We documented that migrants had higher vulnerability for TB, including an increased risk of extrapulmonary TB, multidrug-resistant/rifampicin-resistant TB, TB/HIV co-infection and worse TB treatment outcomes compared to host populations. Consensus recommendations include screening migrants for TB/latent TB infection according to country data, a minimal package for TB care in drug-susceptible and multidrug-resistant/rifampicin-resistant TB, implementation of migrant-sensitive strategies and free healthcare and preventive treatment for migrants with HIV co-infection. Dedicated care for TB prevention and treatment in migrant populations within the European Union/European Economic Area and UK is essential. Key words: tuberculosis, migrants, multi-drug resistance, HIV
Keywords: tuberculosis, migrants, multi-drug resistance, HIV